2008
DOI: 10.1128/jcm.01385-07
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Candida albicans / Candida glabrata Peptide Nucleic Acid Fluorescent In Situ Hybridization Method for Simultaneous Dual-Color Identification of C. albicans and C. glabrata Directly from Blood Culture Bottles

Abstract: We evaluated the performance of the Candida albicans/Candida glabrata peptide nucleic acid fluorescent in situ hybridization (PNA FISH) method, a rapid two-color assay for detection of C. albicans and C. glabrata, in a multicenter study. The assay is designed for use directly from positive blood culture bottles in a FISH format. Intact, fixed cells are labeled fluorescent green (C. albicans) or fluorescent red (C. glabrata) by rRNA hybridization of fluorophore-labeled PNA probes. Results are available <3 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 24 publications
2
90
0
1
Order By: Relevance
“…Many stu di es in dica ted that FISH met hod can iden tify mic ro or ganisms with very high sen si ti vity (100%) and spe ci fi city (100%) and mi xed in fec ti ons can al so be de tec ted by this met hod. [22][23][24] Be si de this, ot her stu - Börekçi ve ark. Enfeksiyon Hastalıkları di es ha ve in di ca ted that PCR-EI A and se mi-nes ted PCR were mo re sen si ti ve than ro u ti ne phe noty pic met hods for the de tec ti on and iden ti fi ca ti on of mic ro or ga nisms in mi xed cul tu res.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many stu di es in dica ted that FISH met hod can iden tify mic ro or ganisms with very high sen si ti vity (100%) and spe ci fi city (100%) and mi xed in fec ti ons can al so be de tec ted by this met hod. [22][23][24] Be si de this, ot her stu - Börekçi ve ark. Enfeksiyon Hastalıkları di es ha ve in di ca ted that PCR-EI A and se mi-nes ted PCR were mo re sen si ti ve than ro u ti ne phe noty pic met hods for the de tec ti on and iden ti fi ca ti on of mic ro or ga nisms in mi xed cul tu res.…”
Section: Discussionmentioning
confidence: 99%
“…21 Se ve ral stu di es ha ve shown that mix tu res of iso la tes in cul tu res can be de tec ted by FISH met hod and FISH is mo re sen siti ve than con ven ti o nal met hods in the de tec ti on of mix tu res of iso la tes in blo od cul tu res. [22][23][24] The aims of this study we re first to in ves ti gate the cli ni cal fe a tu res and risk fac tors in pa ti ents with sing le and mul tip le-spe ci es can di de mi a de tected by FISH met hod. In addition, the epi so des of bre akt hro ugh can di de mi a we re eva lu a ted.…”
Section: Gürol Emekdaşmentioning
confidence: 99%
“…A newer version of this test now allows for the simultaneous identification of either C albicans or C glabrata [16,17].…”
Section: Candidiasismentioning
confidence: 99%
“…• Nonculture Candida detection assays [18][19][20] • The Candida mannan assay yields a sensitivity of 31-90% (less for non-albicans Candida species).…”
Section: Candidiasismentioning
confidence: 99%
“…Recently, ISH techniques employing PNA probes for rRNA have been developed as useful techniques for the differentiation of medically important Candida spp. (11,23). These novel properties enabled PNA probes to hybridize to complementary nucleic acid targets with high specificity and rapid binding kinetics (24,25).…”
mentioning
confidence: 99%